Strategi Pembinaan Kepribadian Berbasis Pondok Pesantren Di Lembaga Pemasyarakatan: Masuk Napi Keluar Santri - Ricky Dwi Prastiyo; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research examines the strategy for developing Islamic boarding schools in correctional institutions. The aim of this research is to formulate a boarding school-based coaching strategy for prisoners in correctional institutions. The research method used is qualitative research with a Library Research approach which in collecting data uses previous research which is still in the same case study in the form of scientific articles. Penitentiary is a place to provide guidance to prisoners with the aim of providing them with provisions to return to society after a prison sentence. The strategies used in Islamic boarding school-based personality development in correctional institutions include; Knowledge or know-ing, implementation or actuating, and habituation or habit. With this strategy, it is hoped that personality development can be more optimal in reconstructing the character and morals of prisoners, before they leave and return to society.